Harnessing the Power of Networks of Care for Universal Health Coverage - Eoghan Brady; Andy E. Carmone; Sarthak Das; Raphael Hurley; Maria Theresa Martinez Vergara; Address Malata (Taylor & Francis Group, 2020)
On the global health agenda, Universal Health Coverage has been displaced by the COVID-19 pandemic while disparities in COVID-19 outcomes have exposed stark gaps in quality, access, equity, and financial risk protection. These disparities highlight the importance of the core goals of Universal Health Coverage and the need for innovative approaches to working toward them. The newly codified concept of "Networks of Care" offers a promising option for implementation. The articles in this special issue present the Networks of Care lexicon and framework and demonstrate the development of leadership, responsibility, intra- and inter-facility cooperation, and dynamic cycles of quality improvement. These elements are associated with better access to services and better health outcomes, the ultimate goals of Universal Health Coverage. Increases in poverty, food insecurity, and deleterious impact on the status of women secondary to the COVID-19 pandemic add urgency to Universal Health Coverage, while the economic impact of pandemic mitigation may reduce availability of resources for years to come. The need for Universal Health Coverage and efficiency and flexibility in health spending, including the ability to contract directly, has become even more important. Countries where Universal Health Coverage efforts have yet to carry through to provision of good quality, accessible and equitable service delivery could potentially benefit from concurrent Networks of Care implementation. Documentation of Networks of Care in the context of Universal Health Coverage should be prioritized to understand how Networks of Care can be used to help realize the goals of Universal Health Coverage around the world.